The Determinant of Decision to Visit Tourism Destination - Wijaya, Nyoman Surya; Sudarmawan, I Wayan Eka; Sukaarnawa, I Gusti Made (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study aims to examine how the decision to visit tourists to tourist destinations Tirta Empul Temple Tampaksiring Gianyar Bali. The dependent variable used in this study is the decision to visit, while promotion, destination attributes and place branding are independent variables. The population of the study were visitors who came to the Tirta Empul Temple Tourism Destination, the research sample was 105 people using accidental sampling technique, with a quantitative descriptive approach, using analytical tools. Partial Least Square (PLS) software SmartPLS. The results of the analysis show promotion and destination attributes have a positive and significant effect on place branding with a value of 7.098 and 6.626, respectively, promotion has a positive and insignificant effect on decisions to visit tourist destinations with a value of 1.603, destination attributes have a positive and significant effect on decisions to visit tourist destinations with a value of 1.603. 3,429, place branding has a positive and significant effect on decisions to visit tourist destinations with a value of 4.646, the formation of place branding is more dominantly influenced by destination attributes, and decision making to visit tourist destinations is more dominantly influenced by place branding. Place Branding acts as a full mediator.